Métodos variacionais aplicados à problemas singulares em equações elípticas não lineares - Brito, Lucas Menezes de (2018)
In this work we study a singular partial differential problem in a bounded domain with smoth boundary. We have two main cases, one superlinear with weak singularity, and the other one sublinear with strong songularity. We use Variational Methods, such as the Ekeland Variational Principle and the Nehari Manifolds, to solve this problem, finding weak solutions and proving the multiplicity of solutions in one of the cases.